Global assessment of lagged and cumulative effects of drought on grassland gross primary production. (March 2022) - Wei, Xiaonan; He, Wei; Zhou, Yanlian; Ju, Weimin; Xiao, Jingfeng; Li, Xing; Liu, Yibo; Xu, Shuhao; Bi, Wenjun; Zhang, Xiaoyu; Cheng, Nuo
Highlights: Lagged and cumulative effects of drought on global grassland GPP are assessed. 74.85% of the grassland shows lagged response to drought, mainly with a time scale of 1 month. 59.06% of the grassland is affected by drought cumulatively, mainly within 2–4 months. The cumulative effect is stronger in relatively arid area than in relatively humid area. Globally, the cumulative effect exceeds the lagged effect for grassland productivity. Abstract: Drought has large impacts on the vegetation growth of global terrestrial ecosystems, particularly grasslands. Extensive in-situ studies have shown that the impact of drought on vegetation growth has lagged and cumulative effects, but it is not well known how grassland productivity (gross primary production or GPP) responds to drought over time at large scales. Here, we investigated the spatiotemporal patterns of lagged and cumulative effects of drought on global grassland GPP using an OCO-2 solar-induced chlorophyll fluorescence (SIF) based GPP product (GOSIF GPP) and the Standardized Precipitation Evapotranspiration Index (SPEI). The results showed that globally, 88.37% of the grassland had a lagged response to drought, with a lagged time scale of mainly 1 month. With the increase in soil water availability, the magnitude of the lagged effect gradually weakened. Grasslands in semiarid and semi humid conditions that were adaptable to periodic drought responded fastest to drought. Globally, more than three quarters (78.55%) of the grassland was affected by the cumulative effect of drought. The accumulated months occurred at longer time scales (8 ∼ 10 months) for the region at 40°N–55°N, which is relatively arid. The cumulative effect in relatively arid areas was stronger than that in relatively humid areas, indicating that grasslands in more arid areas had stronger tolerance to drought. More importantly, we found that the cumulative effect of drought on grassland GPP was stronger than the lagged effect. This study highlights the great importance of considering the legacy effect, especially the cumulative effect, of drought on grassland productivity, which would advance our understanding of the impact of climate change on the carbon and water cycles of terrestrial ecosystems.